THE RELATIONSHIP OF FAT INTAKE AND NUTRITIONAL STATUS IN ADOLESCENT WOMEN OF THE ISLAMIC BOARDING SCHOOL, TUBAN DISTRICT - Nikita Prasiwi; Idcha Kusma Ristanti; Ella Janatul Lailiyah (International Nutrition and Health Administrations Journal, 2024)
Teenagers are one of the groups that easily experience nutritional problems such as malnutrition and overnutrition. Nutritional status is a description of the body's condition as a result of the use of nutrients from the food consumed daily. This research aims to determine the relationship between fat intake and nutritional status in adolescents. Analytical research method with a cross-sectional time approach. The population of this study consisted of 402 respondents with a sample of 200 teenagers, determined using a cluster random sampling technique. The Independent variable is a fat intake, dependent variable is nutritional status. The research analysis uses Spearman's correlation statistical test. The results of the study showed that the majority of adolescent girls' fat intake was higher. Based on the results of statistical tests using the Spearman correlation test for fat intake, a value of p = 0.000 was obtained so that ρ < 0.05, there is a significant relationship between fat intake and nutritional status, the Correlation Coefficient value is in the weak category at 0.312. The conclusion from this study is that there is a significant relationship between fat intake and nutritional status. Keywords: Nutritional Status; Fat Intake; Adolescents.